1915 W.Va. Acts 404, Reg. Sess., Municipal Charters, ch. 11, § 16, pt. 25. - (:unkn) unknown (General Publisher, 1915)
To regulate the keeping, handling and transportation of explosives and dangerous combustibles within the municipality; and to regulate or prohibit the use of fire crackers, sky rockets, toy pistols, air rifles or guns, within the said municipality.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER